A missense mutation in the catalytic domain of O‐GlcNAc transferase links perturbations in protein O‐GlcNAcylation to X‐linked intellectual disability. Issue 4 (7th November 2019) - Pravata, Veronica M.; Gundogdu, Mehmet; Bartual, Sergio G.; Ferenbach, Andrew T.; Stavridis, Marios; Õunap, Katrin; Pajusalu, Sander; Žordania, Riina; Wojcik, Monica H.; van Aalten, Daan M. F.
Abstract : X‐linked intellectual disabilities (XLID) are common developmental disorders. The enzyme O ‐GlcNAc transferase encoded by OGT, a recently discovered XLID gene, attaches O ‐GlcNAc to nuclear and cytoplasmic proteins. As few missense mutations have been described, it is unclear what the aetiology of the patient phenotypes is. Here, we report the discovery of a missense mutation in the catalytic domain of OGT in an XLID patient. X‐ray crystallography reveals that this variant leads to structural rearrangements in the catalytic domain. The mutation reduces in vitro OGT activity on substrate peptides/protein. Mouse embryonic stem cells carrying the mutation reveal reduced O ‐GlcNAcase (OGA) and global O ‐GlcNAc levels. These data suggest a direct link between changes in the O ‐GlcNAcome and intellectual disability observed in patients carrying OGT mutations. Abstract :